The haptics of illusion. An account of touch across theories, technologies and museums (AN-ICON. Studies in Environmental Images [ISSN 2785-7433], 2022)
Touch represents one of the latest and most complex frontiers of virtuality: a sense which historically seems to have carried the burden of proof on reality, by definition resistant to illusory environments. The paper begins from this assumption to trace a history of illusion across authors and theorists that have debated the statute of haptics, building a dialogue between philosophical dilemmas and technological developments. Moving both from an aesthetic and psychophysiological viewpoint, the article will root its analysis in an historical-artistic account, augmenting the discussion with a series of case studies from the museum sector. The introduction of haptic technologies within cultural institutions, which dates back to the last three decades, proves an interesting field to test the functions which touch plays in both educational and imaginative scenarios. The open question being whether modern technologies should aim at replicating haptic realism in miming phenomenological accuracy, or whether the most innovative applications need to aspire to a more environmental employment of touch.
Keywords: Haptic; Technology; Illusion; Virtuality; Museums